Towards increased complexity in Russian regions: networks, diversification and growth - Ivan Lyubimov; Margarita Gvozdeva; Maria Lysyuk (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
Following Hausmann et al. (2011), we apply a network approach to measure the level of economic complexity and diversification opportunities of Russian regions. Using Russian and international export data, we find that the complexity of Russian regional economies varies substantially: rela-tively high in western and central regions, lower in southern and northern Russia and lowest in eastern regions. While Russian regions, on average, have poor diversification opportunities, regions can still diversify their exports by participating in international value-added chains or cooperating in developing group strategies. Our results are highly consistent with two well-established rankings of Russian regional R&D development based on numerous regional indicators, and imply that our network-based measure of complexity captures important features such as the level of regional R&D.
URN:NBN:fi:bof-201804171448
Keywords: O14; O25; R11; 330